2010
DOI: 10.1164/rccm.200903-0415oc
|View full text |Cite
|
Sign up to set email alerts
|

Increase in Exhaled Nitric Oxide Is Associated with Bronchial Hyperresponsiveness among Apprentices

Abstract: Our results suggest that measurement of Fe(NO), a simple and reproducible test, could be useful in the screening of BHR in workers newly exposed to agents known to cause occupational asthma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
2
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 52 publications
2
23
2
3
Order By: Relevance
“…BHR to non-specific bronchoconstrictor stimuli is a key feature of asthma and could be associated with the inflammatory process of the disease. Several studies have shown that BHR to indirect stimuli such as bradykinin, mannitol and adenosine is related to Fe NO or eosinophilic inflammation [12,49,50,51], whilst a relationship between BHR and direct stimuli such as methacholine and Fe NO or eosinophilic inflammation exists [19,52] but is expressed to a lesser extent [51,53] or remains controversial [49,50,54,55]. Finally, on the basis of the present data on Fe NO in BHR-positive compared to BHR-negative patients, it can be postulated that Fe NO might also be a marker potentially able to identify BHR-positive patients with new-onset asthma, and that the link between BHR and Fe NO /eosinophilic inflammation is strictly involved in the pathogenesis of early airflow limitation as detected in newly diagnosed adult asthma cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…BHR to non-specific bronchoconstrictor stimuli is a key feature of asthma and could be associated with the inflammatory process of the disease. Several studies have shown that BHR to indirect stimuli such as bradykinin, mannitol and adenosine is related to Fe NO or eosinophilic inflammation [12,49,50,51], whilst a relationship between BHR and direct stimuli such as methacholine and Fe NO or eosinophilic inflammation exists [19,52] but is expressed to a lesser extent [51,53] or remains controversial [49,50,54,55]. Finally, on the basis of the present data on Fe NO in BHR-positive compared to BHR-negative patients, it can be postulated that Fe NO might also be a marker potentially able to identify BHR-positive patients with new-onset asthma, and that the link between BHR and Fe NO /eosinophilic inflammation is strictly involved in the pathogenesis of early airflow limitation as detected in newly diagnosed adult asthma cases.…”
Section: Discussionmentioning
confidence: 99%
“…Ciprandi et al [18] demonstrated a strong and negative correlation between Fe NO and BHR in asthmatic children; these results confirmed the existence of a link between airway inflammation and BHR. Tossa et al [19] as well proved that an increased Fe NO level was associated with BHR among apprentices.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, these authors concluded that measuring FeNO is a simple and useful test to differentiate AR candidates who will become asthmatics from those with other atopic conditions in a general allergy clinic. Tossa et al [23] investigated a large group of apprentices. The increase in FeNO was associated with the incidence of BHR (odds ratio 2.00) per unit increase in log parts per billion.…”
Section: Discussionmentioning
confidence: 99%
“…However, to-date, there are only a few epidemiological studies (and none among grain workers) using this marker, and the limited evidence available suggests that bronchial hyperresponsiveness is predicted by F E NO increase, rather than by F E NO absolute value [25]. To explore an association between F E NO variation and recent exposure, a study monitoring F E NO values in the same population during the low-exposure season should to be conducted.…”
Section: Discussionmentioning
confidence: 99%